What Affects Perceived Organizational Politics Among Public Health Workers in Zamboanga City, Philippines? - Haictin, Ken M. (Universitas Pancasakti Tegal, 2026)
This research examines the influence of Perceived Organizational Support (POS) on Perceived Organizational Politics (POP), and the mediating role of Public Service Motivation (PSM) on this relationship. An online survey was administered to 85 employees of the Department of Health Zamboanga Peninsula - Center for Health Development in Zamboanga City. The collected data were analyzed using Pearson’s correlation and mediation analyses in Jamovi. The results showed that, while the direct relationship between POS and POP was weak and non-significant, PSM was positively correlated with both constructs. The mediation analysis revealed that PSM acted as a suppressor variable, counteracting the negative effect of POS on POP, indicating that POS paradoxically heightened employees’ sensitivity to organizational politics. Although the findings were limited by sample size and homogeneity, they provided critical insights into employee perceptions in public sector organizations. The results offered a nuanced view of the conventional relationship between POS and POP as opposites along a single continuum; instead, a parallel relationship is possible, especially for employees with high PSM.